Influence Return on Asset and Return on Equity to Return Shares in Registered Companies From Indonesia Stock Exchange - Kurniasih Setyagustina; Dwi Cahyantari Sujono Putri; Zia Ud Din; Wahyudil Khotib; Rama Dhonal (Talaa : Journal of Islamic Finance, 2025)
The aim of this research is to determine the influence between ROA and ROE on Return Shares in companies listed on Idx in 2021-2023, either partially or simultaneously. This research uses an associative quantitative approach because it connects two or more variables. Based on the t test results Return on Asset positive influence on Return Shares, this is seen from the Sig value. for the influence of Return on Equity negative effect on Return Shares, this is seen from the Sig value. for the influence of Return on Asset And Return on Equity simultaneously influence Return Shares, this is seen from the Sig value. 0.008 ≤ 0.05, and calculated F value 5.238 ≥ F table 3.16. So it can be concluded that H0 is rejected and H1 is accepted.